2012
DOI: 10.1007/s12664-012-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Non responsive celiac disease due to coexisting hereditary fructose intolerance

Abstract: Celiac disease is associated with several genetic disorders, but its association with hereditary fructose intolerance is rare. Hereditary fructose intolerance is a rare autosomal recessive disease of fructose metabolism presenting as vomiting after intake of fructose. An association between these two distinct genetic gastrointestinal disorders is important as treatment failure of celiac disease calls for careful evaluation for hereditary fructose intolerance. We report a patient with an association of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Worldwide, common mutations such as p.A149P mutation, which showed a founder effect in studies, have simplified the diagnostic strategy in certain populations (Brooks and Tolan 1993). There is a paucity of literature on HFI and ALDOB gene studies from India, as only few case reports, without mutations, have been reported (Bharadia and Shivpuri 2012;Ananth et al 2003). This is the first report of mutations in the ALDOB gene from India.…”
Section: Discussionmentioning
confidence: 90%
“…Worldwide, common mutations such as p.A149P mutation, which showed a founder effect in studies, have simplified the diagnostic strategy in certain populations (Brooks and Tolan 1993). There is a paucity of literature on HFI and ALDOB gene studies from India, as only few case reports, without mutations, have been reported (Bharadia and Shivpuri 2012;Ananth et al 2003). This is the first report of mutations in the ALDOB gene from India.…”
Section: Discussionmentioning
confidence: 90%
“…To the best of our knowledge, there are only few case reports presenting patients of coexisting CD and HFI [ 15 , 16 , 17 ]. Bharadia et al [ 15 ] reported a case of a 22-month-old boy with recurrent diarrhea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are only few case reports presenting patients of coexisting CD and HFI [ 15 , 16 , 17 ]. Bharadia et al [ 15 ] reported a case of a 22-month-old boy with recurrent diarrhea and vomiting. Duodenal biopsy was assessed as Marsh IIIa (partial villous atrophy, crypt hyperplasia and increased intraepithelial lymphocytes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*********************************************** QNGLVPIVEPEVIPDGDHDLEHCQYVTEKVLAAVYKALNDHHVYLEGTLLSPTW------233 ********************************************** ***.*. There is a paucity of literature on HFI and ALDOB gene studies from India, as only few case reports, without mutations, have been reported (Bharadia and Shivpuri 2012;Ananth et al 2003). Worldwide, common mutations such as p.A149P mutation, which showed a founder effect in studies, have simplified the diagnostic strategy in certain populations (Brooks and Tolan 1993).…”
Section: Discussionmentioning
confidence: 99%